PENGOLAHAN LIMBAH CAIR BATIK MENGGUNAKAN KOMBINASI METODE NETRALISASI DAN ELEKTROKOAGULASI - Dewanti, Beauty Suestining Diyah; Prastiwi, Tafana Firdausi; Sutan Haji, Alexander Tunggul (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI, 2019)
In the process of production, batik industry often used chemicals such as dye used in dyeing process. Waste water of batik industry containing high concentration of BOD, COD, suspended solid, and color relatively high. One of alternative processing for liquid waste batik is using the neutralization and electrocoagulation method. The purposes of this research were to find the influence of processing with the neutralization and electrocoagulation methode , to find the removal efficiency and to know optimal voltage in reducing the concentration of total chromium, COD, and TSS on liquid waste batik. At the neutralization methode using concentrated HCl. Electrode used in electrocoagulation methode was aluminium as plate electrodes. The observation parameter were total chromium, COD, and TSS at 0, 30, 60, and 90 minutes. The process of neutralization and electrocoagulation of liquid waste batik most  effective was reached on voltage 12 volts at 90 minutes that decrease total chromium concentration from 4,908 mg/L to 0,005 mg/L, COD concentration from 1890 mg/L to 68,55 mg/L, and TSS concentration from 296,7 mg/L to 41 mg/L. the voltage as able to produce electrical power equal to 0,036 KWH. A method of electrocoagulation most efficient to remove 99,90%, 96,37%, and 86,18% of total chromium, COD, and TSS respectively. Keywords : Total Chromium, COD, TSS, Liquid Waste Batik, Electrocoagulation